Alteração diferencial nos astrócitos radiais do hipocampo e neurogênese em aves marinhas com rotas migratórias constantes - LIMA, Camila Mendes de (Universidade Federal do Pará, 2019)
Little is known about environmental influences on radial glia–like α cells (radial astrocytes) and their relation to neurogenesis. Because radial glia is involved in adult neurogenesis and astrogenesis, we investigated this association in two migratory shorebird species that complete their autumnal migration using contrasting strategies. Before their flights to South America, the birds stop over at the Bay of Fundy in Canada. From there, the semipalmated sandpiper (Calidris pusilla) crosses the Atlantic Ocean in a non-stop 5-day flight, whereas the semipalmated plover (Charadrius semipalmatus) flies primarily overland with stopovers for rest and feeding. Using hierarchical cluster and discriminant analysis of morphometric features to classify three-dimensionally (3D) reconstructed cells, we identified two morphotypes of radial glia, designated as Type I and Type II. The migratory process affected these cells differentially, with more intense morphological changes in Type I than in Type II morphotypes in both species. We also compared the number of doublecortin (DCX)-immunolabeled neurons with morphometric features of radial glial–like α cells in the hippocampal V region between C. pusilla and C. semipalmatus before and after autumn migration. Compared with migrating birds, the convex hull surface of radial glial–like α cells of wintering birds significantly increased in both C. semipalmatus and C. pusilla. This increase correlated with an increase of the total number of DCX-immunolabeled neurons in wintering birds. The decreased radial astrocyte morphological complexity in the semipalmated sandpiper and its increase in the semipalmated plover, a species that probably relies more on visuospatial information for navigation, may be significant, despite phylogenetic and other differences between these taxa. The migratory flight of the semipalmated plover, with stopovers for feeding and rest, versus the non-stop flight of the semipalmated sandpiper may differentially affect radial astrocyte morphology and neurogenesis.